Novel STXBP1 Mutations in 2 Patients With Early Infantile Epileptic Encephalopathy. (April 2015) - Sampaio, Mafalda; Rocha, Ruben; Biskup, Saskia; Leão, Miguel
The authors describe 2 patients with early infantile epileptic encephalopathy caused by 2 novel mutations involving the STXBP1 gene. The authors suggest that in spite of the rarity of STXBP1 mutations, molecular analysis of STXBP1 gene should be performed in patients with early infantile epileptic encephalopathy, after exclusion of ARX mutations in male patients and CDKL5 mutations in female patients. The potential mechanisms explaining the variable clinical phenotypes caused by STXBP1 mutations are discussed and the designation of early-onset epileptic encephalopathies, including an updated genetic classification, is proposed to encompass the epileptic encephalopathies beginning in the first 6 months of life.